Conceptual and Pedagogical Approaches to the Global Dimension of Youth Work in British Higher Education Institutions. (1st September 2008) - Sallah, Momodou
Global youth work (GYW) may be considered as encompassing forms of education with young people which are variously referred to as development education, global citizenship, education for sustainable development, and humanitarian education amongst others. This article reports on primary research in relation to how GYW is conceptualised and addressed in those Higher Education Institutions (HEIs) that deliver youth and community work qualifications across the UK. The research reports specifically on perceived issues of pedagogy, and asks what skills, knowledge and resources are required to deliver an effective curriculum. The article further explores to what extent HEIs are meeting the needs of the field in regards to addressing a global dimension. The research was based on semi-structured interviews with 43 programme/module leaders in HEIs across Britain, 28 recent youth and community development (YCD) graduates and a focus group comprised of 11 representatives of leading international nongovernmental organisations, HEIs and statutory organisations involved in the delivery of GYW. The research concludes that the conceptualisation of and importance attached to global youth work varies greatly both between and within HEIs. The extent to which current YCD students are enabled to 'think globally and act locally' may be subject to the vagaries of particular tutors' interests. In addition, there is no definitive agreement as to whether lecturers need additional skills to deliver effective GYW training. There is agreement, however, that there is a need for the development of suitable GYW curricula and appropriate learning resources within HEIs delivering youth and community work courses.